El marketing digital y el E-Commerce: herramientas para el fortalecimiento de las empresas agroindustriales del departamento de Cundinamarca (2021)
Agribusiness, known as the primary sector, is the economic activity that is exclusively dedicated to the transformation, production and commercialization of products of agricultural, livestock and livestock inputs, among others, in Colombia this industry is supported by the peasant who takes care of his farm and field, to the great merchant who distributes his products throughout the country. Due to generational changes and technological advances, the production and commercialization processes have been renewed in different ways and because of this the agribusiness has had to transform itself, reinventing itself and updating itself according to the changes that exist in society.